1990
DOI: 10.1007/bf00223799
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure and locomotor activity in mice selected for food intake adjusted for body weight

Abstract: The aim of this study was to examine the differences in physical activity and their contribution to differences in energy utilization in mice, selected either high or low for food intake, adjusted for body weight, which show correlated responses in lean content and metabolic rate. Simultaneous measurements of fasting metabolic rate and activity were made in lines of mice selected at either: a young age, 4-to 6-week food intake corrected for 4-week body weight; or an older age, 8- to 10-week food intake correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Few studies evaluated both sexes for activity level, and of those that did, even fewer included it as an effect in their model. Moruppa (1990) found that male mice were more active than females at young (3-to 4-wk) and old (10-to 11-wk) ages. This is contrary to our findings, but Moruppa (1990) measured for only a 3-h period during the lighted part of the day.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies evaluated both sexes for activity level, and of those that did, even fewer included it as an effect in their model. Moruppa (1990) found that male mice were more active than females at young (3-to 4-wk) and old (10-to 11-wk) ages. This is contrary to our findings, but Moruppa (1990) measured for only a 3-h period during the lighted part of the day.…”
Section: Resultsmentioning
confidence: 99%
“…Moruppa (1990) found that male mice were more active than females at young (3-to 4-wk) and old (10-to 11-wk) ages. This is contrary to our findings, but Moruppa (1990) measured for only a 3-h period during the lighted part of the day. However, cattle data reported by Voisinet et al (1997) agree with this study; heifers were more active (temperamental) than steers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations